Assessing the impact of participatory research in rice breeding on women farmers: a case study in eastern Uttar Pradesh, India - Paris, Thelma R.; SINGH, ABHA; CUENO, AMELIA D.; SINGH, V.N. (Cambridge University Press, 2008)
This paper assesses farmer adoption of rice varieties and new genotypes introduced through participatory varietal selection (PVS) in villages which represent submergence- and drought/submergence-prone villages in eastern Uttar Pradesh, India. It focuses on the involvement of women farmers in participatory research for screening improved varieties for areas which suffer from abiotic stresses. It further assesses the impact on the decision-making authority (or women's empowerment) on rice varietal choice, seed acquisition and disposal, and crop management after participating in PVS trials. It suggests strategies to empower women farmers in making sound and timely decisions on farm-related matters and to enhance their roles in accelerating the adoption of new varieties.